Complications and Management of Eptifibatide-Induced Thrombocytopenia. Issue 12 (December 2021) - Masood, Faisal; Hashmi, Saad; Chaus, Adib; Hertsberg, Anna; Ehrenpreis, Eli D.
Background: Eptifibatide is used in acute coronary syndromes to reversibly block platelet aggregation by inhibiting the platelet glycoprotein IIb/IIIa receptor. A serious adverse effect of eptifibatide is a profound drop in platelet count, termed eptifibatide-induced thrombocytopenia (EIT). Objective: To provide insight into the types of complications and management of EIT. Methods: Cases of EIT submitted to the Food and Drug Administration adverse event reporting system were evaluated. Data analyses included management of EIT, complications of thrombocytopenia, initial platelets, and platelet nadir following eptifibatide. Results: 103 cases of EIT were reported from January 2010 to 2019; 57 cases met the Naranjo scale and were included. Only 37 of those cases contained information on how EIT was managed. Eptifibatide administration was withheld in all 37 of those cases. Platelet transfusions were administered in 20 cases (54%). Two cases were managed with steroids (5.4%), and 1 case used intravenous immunoglobulin G to reverse EIT (2%). The median initial platelet count prior to administration of eptifibatide was 207 000 cells/mm 3 (SD = 69 000; n = 27), and median platelet nadir was 9000 cells/mm 3 (SD = 19 000; n = 35) The majority of complications of EIT included bleeding events (16/28, 57%). Delayed procedures, prolonged stay, allergic reactions, and thrombosis were each reported in 3 patients (10.75%). Conclusion and Relevance: Most cases of EIT were managed by withholding eptifibatide with platelet transfusion if necessary. The majority of complications included bleeding. However, significant procedure delays, prolonged hospital stay, thrombosis, and allergic reactions were also reported.